Swarming Motility Without Flagellar Motor Switching by Reversal of Swimming Direction in E. coli - Wu, Zhengyu; He, Rui; Zhang, Rongjing; Yuan, Junhua (Frontiers in Microbiology, 2020)
In a crowded environment such as a bacterial swarm, cells frequently got jammed and came to a stop, but were able to escape the traps by backing up in their moving course with a head-to-tail change (a reversal). Reversals are essential for the expansion of a bacterial swarm. Reversal for a wildtype cell usually involved polymorphic transformation of the flagellar filaments induced by directional switching of the flagellar motors. Here we discovered a new way of reversal in cells without motor switching and characterized its mechanisms. We further found that this type of reversal was not limited to swarmer cells, but also occurred for cells grown in a bulk solution. Therefore, reversal was a general way of escaping when cells got jammed in their natural complex habitats. The new way of reversal we discovered here offered a general strategy for cells to escape traps and explore their environment.